PERTEMPURAN TANAH ARON - Ida Bagus Astika Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
The research aims to uncover the Battle of Tanah Aron and the efforts made in that battle. The method used is the Historical Method. The research results show that when Indonesia was proclaimed by Ir. Sukarno accompanied by Drs. Mohammad Hatta on August 17 1945, the news was not immediately known due to lack of communication and transportation at that time. The news only became known after Mr. I Gusti Ketut Puja as the representative of Sunda Kecil in PPKI returned to Jakarta. NICA (the Netherlands) wanted to regain control of Bali. People resistance arose under the leadership of I Gusti Ngurah Rai. To increase people's enthusiasm for facing NICA and divert their attention, I Gusti Ngurah Rai decided on July 28 1946 to hold a "June-July Journey". The trip aims to make it easier for aid from Java to enter Bali. The journey starts from Bengkel Anyar Village by climbing Mount Batukaru towards Buleleng and continuing east towards Mount Agung. Throughout the journey, the main troops led by I Gusti Ngurah Rai continued to experience fighting. The peak occurred in the Tanah Aron area on July 7 1946, when 82 NICA soldiers were killed. As a result of its defeat, NICA launched an onslaught. For this reason, the main troops were ordered to retreat by climbing Mount Agung. On July 23 1946 in Munduk Pengorengan a meeting of the MBO leadership was held. The results of the meeting decided that the troops would return to repair their respective areas.